2016
DOI: 10.21809/rilemtechlett.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Application of bacteria in concrete: a critical evaluation of the current status

Abstract: Microbially induced carbonate precipitation has been tested over more than a decade as a technique to enhance concrete properties. Mainly bacteria following the pathways of urea decomposition, oxidation of organic acids, or nitrate reduction have been studied for this purpose. For bacteria mixed into fresh concrete, it is difficult to prove that they actively contribute to calcium carbonate precipitation and the effects on concrete strength are variable. Application of bacteria for surface consolidation has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 36 publications
0
31
1
Order By: Relevance
“…The self-healing control tested in this study was significant to reveal the sole effect of microbial induced crack healing on the corrosion behaviour of the steel. Obtained results revealed that only biomineralization is not an effective method for protection of the steel reinforcement as opposed to the claims in previous microbe-based self-healing studies 46,9,14 . Corrosion of the steel reinforcement in self-healing control continued even after the noted complete crack closure on day 28.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The self-healing control tested in this study was significant to reveal the sole effect of microbial induced crack healing on the corrosion behaviour of the steel. Obtained results revealed that only biomineralization is not an effective method for protection of the steel reinforcement as opposed to the claims in previous microbe-based self-healing studies 46,9,14 . Corrosion of the steel reinforcement in self-healing control continued even after the noted complete crack closure on day 28.…”
Section: Discussioncontrasting
confidence: 73%
“…Such regain in functionality is desired to hinder the ingress of aforementioned aggressive substances and to protect the good state of the rebar 11–13 . In previous microbe-based self-healing studies, it was claimed that biomineralization in microcracks is an effective method for protection of the steel reinforcement 46,9,14 . Yet, available data lacks solid evidence on the protective effect of MSCC against rebar corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Limestone, or calcium carbonate, is a concrete compatible material that is perfectly suitable for sealing (waterproofing) of cracks in concrete. Several research groups worldwide have developed bacteria-based healing agents to enhance the self-healing capacity of cement pasts, mortars and concrete [7][8][9][10][11][12]. Pioneering and lab-based research by the Delft research group has shown that lactate-based organic compounds like calcium lactate and lactide-polymers) are suitable carbon sources for the bacteria and that these compounds are furthermore concrete compatible in the sense that they as additive, within limits, do not negatively affect strength development of concrete [7, 8 13,14].…”
Section: Autonomous Crack Repair By Limestoneforming Bacteriamentioning
confidence: 99%
“…It is possible to lower the cost of the method by optimizing the concentration of urease and carbonate. However, calcium carbonate is hygroscopic, which triggers high probability of damage in the stone [8].…”
Section: Introductionmentioning
confidence: 99%
“…Microbially induced calcium carbonate precipitation (MICP) in environmental engineering has been studied mainly for crack remediation in concrete, soil improvement and application in the fields of surface protection of natural stone [8]. MICP as a new technique in engineering is better than conventional chemical methods, which are environmentally harmful, often toxic and expensive [1,7].…”
Section: Introductionmentioning
confidence: 99%